Vienna lectures on legal philosophy - Bezemek, Christoph; Potacs, Michael; Somek, Alexander, 1961- (Portland, Oregon : Hart Publishing, 2020)
"The first volume of the Vienna Lectures on Legal Philosophy illustrates the remarkable scope of contemporary legal philosophy. It introduces methodological questions rooted in national academic discourses, discusses the origin of legal systems, and contrasts constitutionalist and monist approaches to the rule of law with the institutionalist approach most prominently and vigorously defended by Carl Schmitt. The issue at the core of these topics is which of these perspectives is more plausible in an age defined both by a 'postnational constellation' and the re-emergence of nationalist tendencies; an age in which the law increasingly cancels out borders only to see new frontiers erected."
Volume 1 Legal positivism, institutionalism and globalisation.
Volume 1: Legal positivism, institutionalism and globalization.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law -- Philosophy; Law -- Methodology; Law; Electronic books